Effect of the wetland environment on particulate matter and dry deposition. Issue 8 (2nd April 2020) - Yang, Tingyu; Wang, Yu; Wu, Yanan; Zhai, Jiexiu; Cong, Ling; Yan, Guoxin; Zhang, Zhenming; Li, Chunyi
ABSTRACT: In Beijing, particulate matter (PM) in the atmosphere, especially PM2.5 and PM10, have attracted public attention because of its adverse effects. A series of studies have investigated the sources and spatial–temporal variation of PM. Wetland has been reported to own the capacity of resolving air problem. To examine the characteristics of the particulate matter in wetlands, the diurnal variation of PM2.5 and PM10 concentrations with respect to two heights (i.e. 1.5 and 10 m, respectively) and three meteorological factors (i.e. wind speed, temperature, and relative humidity, respectively) was monitored in the Cuihu National Wetland Park in Beijing, and the dry deposition velocity and flux were analysed using the above-mentioned data. Results indicated that (1) As for diurnal variation, the PM concentration constantly decreased at 07:00–16:00 and gradually increased at 16:00–18:00. The maximum instantaneous concentration was observed at 07:00–10:00, while the minimum instantaneous concentration was observed at 13:00–16:00. (2) The annual concentration variation of PM followed the order of dry period > wet period > normal period. (3) The particulate concentrations at 10 m were always greater than those at 1.5 m. (4) The PM concentration was positively correlated to the relative humidity and negatively correlated to the temperature. Wind speed exhibited a complex effect on PM concentration. (5) The regulation of dry deposition efficiency followed the order of spring > winter > summer. (6) Wind speed strongly and positively affected the dry deposition velocity of PM10. The effects of temperature and relative humidity on dry deposition were uncertain. GRAPHICAL ABSTRACT: